(untitled) (Nóema, 2021)
The article tries to give the sense of the ecological perspective of Ivan Illich, a radical thinker and critic of modernity, which he considers the result of the evangelical message’s perversion, operated by the Roman Church. Industrialization, conceived as the ultimate effect of that betrayal, condemns the human being to a condition of dependence and subordination to the goods produced on the market and the services offered by the categories of competent experts. In this way, according to Illich, he compromises his relationship with others and with the Earth as his home, locking himself in the shell of his own individuality, a prisoner of the needs created by the market. For Illich, restoring the ecological balance is possible only through a substantial change in production rhythms, in order to restore man’s mastery of the tools and his own autonomy.